PROCEEDING IN THE CIVIL COURTS OF THE REPUBLIC OF UZBEKISTAN ON ISSUING A WRIT OF EXECUTION FOR COMPULSORY EXECUTION OF THE ARBITRATION DECISION - Akramov , Alisher Akbar o‘g‘li (Educational Research in Universal Sciences, 2023)
In this article, in the Civil Courts of the Republic of Uzbekistan, the proceedings on the issuance of a writ of execution for the mandatory execution of the decision of the Arbitration Court are analyzed through the norms of the existing legal documents in the Republic of Uzbekistan and the information cited in the scientific literature. and it is explained by what methods and means these cases are regulated in our country. Also, the views of a number of legal scholars were highlighted, and some problems existing in this system in our country were discussed.